Home-Based Modification Approaches for Children with Autism (3–18 Years): A Scoping Review - Golnaz Ahmadi; Nazila Akbarfahimi; Navid Mirzakhani Araghi (Journal of Rehabilitation Sciences and Research, 2025)
Background: Creating a calm and supportive home environment is vital for children with Autism Spectrum Disorder (ASD) and their families. This scoping review aimed to examine the impact of personalized home-based modifications on the well-being and development of children with ASD. Methods: Following the PRISMA-ScR guidelines, a comprehensive literature search was conducted across PubMed, Cochrane, ScienceDirect, and Scopus databases through June 2023. Emphasis was placed on key concepts related to home-based interventions for children aged 3 to 18 with ASD. From an initial pool of 6,022 articles, 23 relevant studies, including reviews, were selected for inclusion. Results: Home-based modifications—including behavioral, sensory, and technological interventions—are prevalent and contribute to enhancing the quality of life for children with Autism Spectrum Disorder (ASD) while promoting their independence. This study underscores the importance of individualized living spaces and advocates for further research into integrating technology and architectural design within home environments. These findings provide valuable insights for healthcare professionals and caregivers. Conclusion: Establishing a safe and supportive home environment for children with ASD is crucial. Tailored home modifications have been shown to improve their quality of life. Future research exploring architectural strategies, targeted interventions, and the integration of assistive technologies within home settings is recommended to further support children with ASD.